Pathophysiological Mechanisms and Potential Therapeutic Targets in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy (CADASIL) - Locatelli, Martina; Padovani, Alessandro; Pezzini, Alessandro (Frontiers in Pharmacology, 2020)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), is a hereditary small-vessels angiopathy caused by mutations in the NOTCH 3 gene, located on chromosome 19, usually affecting middle-ages adults, whose clinical manifestations include migraine with aura, recurrent strokes, mood disorders and cognitive impairment leading to dementia and disability. In this review, we provide an overview of the current knowledge on the pathogenic mechanisms underlying the disease, focus on the corresponding therapeutic targets, and discuss the most promising treatment strategies currently under investigations. The hypothesis that CADASIL is an appropriate model to explore the pathogenesis of sporadic cerebral small vessel disease is also reviewed.